Pemanfaatan Limbah Padat Aren dengan Pengaya Nutrisi Pupuk terhadap Pertumbuhan dan Hasil Tomat - Supriyono Supriyono; Rahayu Rahayu; Latif Munawar (Universitas Sebelas Maret, 2016)
Palm sugar solid waste create problem for local resident. Palm sugar liquid waste is one of the material that could potentially be used as an organic fertilizer. This study aims to obtain an organic fertilizer that can increase growth and yield of tomatoes. This study was held in the greenhouse of Faculty of Agriculture, Sebelas Maret of University (UNS). The study used Randomized Block Design Complete (RCBD) with one factor, that is the composition of organic fertilizer consisted of control (P0), palm sugar solid waste with cattle stool (P1), palm sugar solid waste with goat stool (P2), palm sugar solid waste with chicken stool (P3), palm sugar solid waste with quail stool (P4), palm sugar solid waste with bran (P5). Each treatment was repeated 4 times. Data were analyzed using ANOVA and be continued with Least Significant Differences (LSD). The result show that application of organic fertilzer from palm sugar solid waste with bran can increase growth and yield of tomatoes.